Pengaruh Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR) dan Net Interest Margin (NIM) Terhadap Return on Asset (ROA) (Studi Kasus Pada Bank Umum yang Listed di Bursa Efek Indonesia Tahun 2019-2023) - A, Dhea Ayu Recita Dwi Putri.; Bella, Cinthya (Gorontalo State University, 2025)
The objective of this study is to evaluate the extent to which the Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM) influence the financial performance of commercial banks, particularly Return on Assets (ROA), among banks listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The researchers employed a quantitative approach, utilizing EViews 12 software for data analysis. Using the purposive sampling technique, 13 bank samples were selected based on specific criteria. Among the four variables examined, CAR and NIM were found to have a statistically positive impact on ROA, as revealed by the study. In contrast, NPL and LDR did not significantly affect bank profitability as measured by ROA. Thus, the analysis suggests that strengthening capital adequacy and optimizing interest income efficiency play a more substantial role in enhancing bank financial performance compared to credit risk (NPL) and liquidity management (LDR).